Pemberdayaan Masyarakat Desa melalui Budidaya dan Pengolahan Toga sebagai Alternatif Obat Herbal Keluarga - Desy Fadilah Adina Putri; Hamidatun Rabayya Yusuf; Wa Ode Nanang Trisna Dewi (CV. ALIM'SPUBLISHING, 2026)
Utilization of Family Medicinal Plants (TOGA) is a strategy that is in line with the concept back to nature and family health independence. Rural communities' dependence on synthetic chemical drugs often faces obstacles such as limited access, high costs, and potential side effects, even though Indonesia is rich in medicinal plant biodiversity that has not been optimally utilized. This Community Service (PkM) activity aims to improve the health and economic independence of residents of Pungkit Village, Lopok District, through the optimization of TOGA. The implementation method is based on structured empowerment that includes four main stages: socialization of the importance of